Tourism Amenities in Shadhapathor (White Stone), Sylhet: A Demographic Outlook of Visitors - Kabir, Mohammad Rezaul; Hossain, Moshin; Begum, Syeda Afsana (Future Science / FSH-PH Publications, 2025)
Tourism is a crucial aspect of a nation's social and economic life as it helps people break away from monotonous lives and contributes to the state's economic development. Tourism amenities such as security, natural beauty, hotel and motel accommodations, and transportation facilities are essential for tourists attraction. However, the visitors demographic characteristics have an impact on the tourism site they choose. The primary goal of this study is to examine the demographic characteristics of visitors and their opinions of the tourism facilities at the Shadapathor tourist destination in Sylhet. This study used primary data, which was collected from 200 visitors using a questionnaire survey. Descriptive and cross-tabulation analysis were used to present the data. According to the survey, the majority of the visitors were male from urban regions; their ages ranged from 17 to 45; they were single; they had postgraduate to HSC degrees; they were employed as students or service providers; and their income was between BDT 20000 and BDT 40000. The study also revealed that while the area's natural beauty greatly pleased all tourists, there are still room for improvement regarding supplemental services, hotel, motel, restaurant facilities, security, and transportation. It has also been revealed that Shadapathor meets all the requirements to be considered one of Bangladesh's top tourist destinations, regardless of amenities. The demographic status of Shadhapathor visitors was showing through this study survey, with the majority being educated, with an average income level, and belonging to the middle-aged group of national visitors.While foreign visitors rarely visit this spot. The results aid in identifying tourist market segments and comprehending their demand by authorities and organizations.